Central Subclavian Catheterization in Newborns: Single-Center Experience - Gurel, Selcuk; Gözen, Ahmet; Bektas, Mehmet Selcuk (Journal of Child Science, 2022)
Our main aim of this article was to show that central venous catheter (CVC) can be an easy-to-use, less-complicated catheter application such as peripherally inserted central catheter and umbilical catheter placement in the neonatal intensive care unit. We here described our experience with subclavian vein catheterization. Neonates who had venous access through subclavian central catheterization were assessed retrospectively. Data such as gestational age, age at the time of catheter insertion, birth weight, and gender were collected. In addition, problems related to catheterization during hospitalization were documented. This study comprised 40 newborns, 22 male and 18 female, with a mean gestational week of 29.57 ± 3.80 weeks and a mean gestational weight of 2067.50 ± 545.97 g. Due to occlusion, catheters were switched in five cases twice and in three cases once, totaling 53 catheterizations on 40 newborns. None of our patients had pneumothorax or hemothorax. On the postoperative 8th and 21st days, the catheter was withdrawn due to catheter infection in two (5%) patients, and catheter cultures revealed coagulase negative Staphylococcus aureus in both cases. Even in preterm infants, subclavian central venous catheterization is a safe and straightforward technique of gaining venous access in expert hands in the neonatal intensive care unit.
Keywords: newborn; CVC; NICU; catheterization